2020
DOI: 10.1590/0034-7167-2018-0177
|View full text |Cite
|
Sign up to set email alerts
|

Nursing care in mental health based on the TIDAL MODEL: an integrative review

Abstract: Objectives: to identify the applicability of the Phil Barker’s Tidal Model in mental health nursing care. Methods: an integrative literature review carried out by LILACS, MEDLINE, Scopus and Web of Science. Data were collected from December 2017 to March 2018. After selecting the studies, the sample totaled 24 articles. Results: the articles are in English (91.7%), were published in nursing journals (87.5%), are reflective and/or theoretical (50%) and have level of evidence VII (79.2%). The model brings cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
17

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 26 publications
0
17
0
17
Order By: Relevance
“…Moreover, most patients do not know enough about treatment knowledge, resulting in negative emotions [17][18][19]. Relevant studies have shown that the common problems in hemodialysis patients are anxiety and depression, which seriously affect the treatment of patients [20,21]. How to reduce patients' negative emotions through effective nursing has become a key topic of clinical medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most patients do not know enough about treatment knowledge, resulting in negative emotions [17][18][19]. Relevant studies have shown that the common problems in hemodialysis patients are anxiety and depression, which seriously affect the treatment of patients [20,21]. How to reduce patients' negative emotions through effective nursing has become a key topic of clinical medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…The Tidal Model has influences from other Nursing theorists, such as Hildegard Peplau and Joyce Travelbee, indicating a position within the field of interactionist theories. As it is a middle-range theory, with fewer concepts and less abstraction, it becomes advantageous for implementation in the care routine (3,8) . This implementation of care seems to be being materialized, considering its application in several countries, such as Australia, Canada, New Zealand, Japan, Scotland and Wales.…”
Section: The Tidal Modelmentioning
confidence: 99%
“…As a way of providing new subsidies to understand the phenomenon of psychosis in the context of mental health, the Tidal Model is used as a theoretical framework that considers the human experience as something natural, with its own flow and in constant change. This theory values the singularity of the person and their capacity for intrinsic resolution, enabling the achievement of new horizons of human experience (3)(4)(5) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations